PENDEKATAN DAKWAH K.H. MARZUKI MUSTAMAR DALAM MEMPERKOKOH AQIDAH AHLUSSUNNAH WAL JAMA’AH AN-NAHDLIYAH MASYARAKAT DAN SANTRI PONDOK PESANTREN SABILURROSYAD MALANG - Sodikin, Ali (MIYAH : Jurnal Studi Islam, 2023)
Abstrak: Currently, there is a charismatic Kiai who is nicknamed "Hujjatu NU" in Malang, because of his expertise in defending and strengthening the Islamic teachings of Ahlussunnah Wal Jama'ah an-Nahdliyah which are considered heretical by other ideologies. It is K.H. Marzuki Mustamar, one of the kiai who preaches in strengthening and defending the beliefs of Ahlussunnah Wal Jama'ah An-Nahdliyah. To find out the da'wah approach, its supporting and inhibiting factors, two problem formulations emerged in this research, namely; (1) What Da'wah Approach is used by. K.H. Marzuki Mustamar in Strengthening the Aqidah of Ahlussunnah Wal Jama'ah An-Nahdliyah Community and Students of the Sabilurrosyad Gasek Sukun Malang Islamic Boarding School? (2) What are the supporting and inhibiting factors experienced by K.H.Marzuki Mustamar in strengthening the Aqidah of the Ahlussunnah Wal Jama'ah an-Nahdliyyah community and the students of the Sabilurrosyad Gasek Sukun Malang Islamic Boarding School?. The results of this research show that Kiai Marzuki Mustamar's preaching approach uses an educational approach. Cultural, and psychological. Meanwhile, the supporting and inhibiting factors experienced by K.H. Marzuki are as follows: Supporting factors include; Sincere intentions, his knowledge or wisdom regarding religious knowledge, encouragement from his family and students, his network is very wide and support from the local government, and he is motivated by Mbah Hasyim's words "whoever brings NU to life, I will admit to being my student". Meanwhile, the inhibiting factor is the amount of terror that is disturbing. Kata kunci: Da'wah, Da'wah Approach, Aqidah Ahlussunnah Wal Jama'ah An-Nahdliyah